2021
DOI: 10.14488/bjopm.2021.034
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic and construction industry: Impacts, emerging construction safety practices, and proposed crisis management

Abstract: Goal: COVID-19 has a drastic effect on world economic progress and different industries. As the main contributor to countries' economies, the construction industry faced multiple challenges due to pandemics. Therefore, it's essential to identify the impact of COVID-19 on the construction sector and develop safety practices in construction processes. This study proposed necessary construction practices and a crisis management framework needs to adopt in the COVID-19 scenario.Design / Methodology / Approach: At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 34 publications
0
52
0
Order By: Relevance
“…Formed by companies of different sizes and technologies, the Brazilian construction sector was directly impacted by the global crisis in the 2020s [42]; the pandemic's impact was also nationally confirmed by Baqui et al [43], Bartik et al [44], and others. Regarding timber housing, the Brazilian sector is more vulnerable than the construction industry in general since this specific activity is predominated by compact-to-medium-sized companies, as examined by De Araujo et al [45], being driven by visible commerce as observed by De Araujo et al [23].…”
Section: Timber Construction and The Demand About Its Electronic Marketmentioning
confidence: 92%
“…Formed by companies of different sizes and technologies, the Brazilian construction sector was directly impacted by the global crisis in the 2020s [42]; the pandemic's impact was also nationally confirmed by Baqui et al [43], Bartik et al [44], and others. Regarding timber housing, the Brazilian sector is more vulnerable than the construction industry in general since this specific activity is predominated by compact-to-medium-sized companies, as examined by De Araujo et al [45], being driven by visible commerce as observed by De Araujo et al [23].…”
Section: Timber Construction and The Demand About Its Electronic Marketmentioning
confidence: 92%
“…(Akinbami and Lawal 2009). The comparison of the construction sector with other industrial sectors showed that the construction sector faced a lot of pressure and criticism to implement eco-friendly techniques and practices because of the hazardous environment (Gao et al 2021;Iqbal et al 2021a). Enshassi and Mayer (2005) suggested that customers establish strict environmental demands to exert pressure regarding EMP adoption in construction projects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Usmani et al (2022) stated that FDM is the best-known technique to analyze, arrange, and structure inputs from the experts. This allows experts to adjust their responses and reduce the number of variables influencing and obtaining the most relevant variables (Iqbal et al 2021a;. Hussain et al, (2019) identified that this approach assists to get a consensus among respondents…”
Section: Emps Adoption Driversmentioning
confidence: 99%
See 1 more Smart Citation
“…Refs. [46][47][48][49] stated that ISM transforms erroneous and unclear models into precise and visible models. Different studies employing ISM and MICMAC techniques are listed in Table 3.…”
Section: Interpretive Structural Modeling (Ism)mentioning
confidence: 99%